Leaching of a low-grade, copper-nickel sulfide ore. 3. Interactions of Cu with selected sulfide minerals - Maley, Mark; Van Bronswijk, Wilhelm; Watling, H. (Elsevier Science BV, 2009)
Interactions between copper ions and selected sulfide mineral concentrates were investigated in flask and column tests under conditions relevant to heap leaching in order to understand why copper recovery from a copper-nickel complex sulfide ore was significantly less than nickel recovery. Both pyrrhotite and pyrite were found to play roles in copper deposition from sulfate solutions in the range pH 1-5. The non-oxidative dissolution of pyrrhotite, previously reported to occur under acidic conditions of low oxygen availability, was also found to occur in a well-aerated system. Soluble copper reacted with the generated hydrogen sulfide to form copper sulfide, mainly covellite at pH >2.3 and its re-dissolution required acid, oxygen and a strong oxidant such as ferric ion. While significant copper also precipitated from copper sulfate solutions pH N3 in the presence of pyrite, the brochantite which was formed was readily re-dissolved at pH <3. The poor recovery of copper experienced in a test heap of copper-nickel sulfide ore was attributed to the presence of pyrrhotite and the rise in pH as the leachate percolated through the heap bed. The copper would only be recovered if acidic, oxidising conditions were restored in the heap.